Peningkatan Partisipasi Masyarakat untuk Percepatan Capaian SDG’s Sektor Air Bersih dan Sanitasi - Sri Hartati Dewi; Harmiyati; Vauzhea Sherlina; Gryanda Wahyu Sugeng; Bismi Annisa (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The SDGs or Sustainable Development Goals are the 2030 Global Development Agenda which has become a commitment from all countries in the world, including Indonesia. Goal 6 Clean water and sanitation aims to ensure the need for clean water is adequate for all levels of society. Achieving these goals is highly dependent on community participation to help accelerate the SDG's program in the clean water and sanitation sector. The need for clean water can be met by utilizing the existing clean water supply while taking into account the impact on the environment. Rainwater has the potential to become a clean water resource by utilizing a simple rainwater harvesting system consisting of gutters, piping systems, and water tanks. By utilizing rainwater resources, it can help reduce the use of groundwater due to overexploitation of groundwater. Service activities are carried out online and offline together with partners SMPN 06 Pekanbaru by build Rain Water Harvesting (RWH) construction; so that later the RWH building can become a pilot activity/ best practice for other schools and the surrounding community.